معادلات الانحدار غير المرتبطة ظاهريا (توزيع المتغيرات والخطأ بواسون) - جواد, فاطمة عبد الحميد (Journal of Economics and Administrative Sciences, 2010)
This study is about finding the estimation of tow equations, the comparative has been done between the estimations  by using seemingly unrelated regression equations for the variable and random error has been distribution with poisson and the variable and random error has been distribution with normal and the method by using oldenary lest square.While in the application side, we have estimated the parameter of investment specification function for the sector of agriculture with the industry sector is enabled us to obtain an estimation efficiency for the model of seemingly unrelated Poisson regression equation. المستخلص